The Development of the Himpunan Mahasiswa Islam Organization in Medan City Post-Reformation - Achiriah Achiriah; Muhammad Ridho Azhar (Yupa: Historical Studies Journal, 2023)
The present study aims to analyze Himpunan Mahasiswa Islam's (HMI) development in Medan City after the reform era, employing a qualitative research design with a case study approach. This study showcases that HMI has developed significantly through in-depth interviews, document analysis, and field observations. The organization has demonstrated its ability to adapt to social, political, and cultural changes. HMI proactively participates in a wide range of social, political, and religious activities that contribute to the betterment of students, campuses, and the local community. By serving as a platform for political education, HMI in Medan City plays a pivotal role in facilitating thoughtful discussions and fostering the advancement of Islamic thought. Moreover, it acts as a catalyst for promoting constructive social change within its sphere of influence. HMI is firmly dedicated to promoting education, protecting students’ rights, and actively advocating for political and social reforms in Indonesia. This research offers valuable insights into the development of HMI in Medan City after the reform era, thereby contributing significantly to the comprehension of the role and potential of student organizations in driving social and political changes in Indonesia.